Efficient degradation of Bisphenol A by Fe3+/Fe2+ cycle activating persulfate with the assistance of biochar-supported MoO2 - Ouyang, Da; Wu, Ronghao; Xu, Zhaojun; Zhu, Xiaomin; Cai, Yimin; Chen, Ruihuan; Zhu, Changyin; Barceló, Damià; Zhang, Haibo (Chemical engineering journal (Lausanne, Switzerland : 1996), 2023)
[Display omitted] •Biochar-supported MoO2 (MoO2@BC) significantly promotes the Fe3+/Fe2+ conversion.•Bisphenol A (BPA) is efficiently removed within the MoO2@BC/Fe3+/PDS system.•Biochar facilitates the Fe3+ adsorption on biochar surface and the electron transfer from Mo(IV) to Fe3+.•Both SO4−, OH and 1O2 are responsible for the BPA degradation. Advanced oxidation processes (AOPs) based on persulfate (PDS) activation by iron materials have attracted significant attention due to their high organic pollution removal efficiency and relatively low remediation costs. However, one of the iron-based materials’ shortcomings is the weak activation ability of Fe3+ on PDS and the low sustainability of Fe2+ in the oxidation environment. In this study, biochar-supported molybdenum dioxide (MoO2@BC) was employed as a co-catalyst to enhance the Fe3+ based PDS activation for Bisphenol A (BPA) degradation. Results showed that >96 % of BPA was removed during 60 min, and the BPA degradation efficiencies only slightly decreased after four reuses of MoO2@BC. Electron paramagnetic resonance (EPR) analysis and quenching experiments indicated that reactive oxidation species (ROSs) contributing to the degradation of BPA were SO4−, OH and 1O2. Besides, it was found that biochar supporting favours the adsorption of Fe3+ on the MoO2 surface and promotes the electron transfer from Mo(IV) to Fe3+ based on the combination of X-ray photoelectron spectroscopy (XPS) analysis, electrochemical tests and density functional theory calculation (DFT). This work provides a new insight for enhancing the performance of organic contaminants degradation through AOPs based on persulfate activation by iron material.